Horticultural activity in soil inoculated with Streptomyces rimosus improved depressive mood with altered electroencephalogram and serum metabolism in adults - Risu Kim; Sowon Yang; Choong Hwan Lee; Sin-Ae Park (Scientific Reports)
Abstract This study investigated the psychophysiological and metabolomic changes during horticultural activities involving the inhalation of volatile organic compounds (VOCs) in individuals experiencing depressive mood based on the presence or absence of the soil microbe Streptomyces rimosus, which emits VOCs. Thirty participants met the specific depression and anxiety criteria and engaged in horticultural activities using soil inoculated with S. rimosus (experimental group) or medium (control group). Electroencephalogram (EEG) was used to analyze the resulting psychophysiological response, and blood samples were collected after each activity. Significant increases were observed in the FZ channel of the central frontal lobe for relative theta, relative alpha, relative slow alpha, ratio of sensorimotor rhythm mid beta to theta, and ratio of alpha to high beta, whereas significant decreases were noted for relative beta, relative high beta, and relative gamma and spectral edge frequency 50% and 90%. GC-TOF-MS analysis identified 44 altered serum metabolites, showing an increasing trend in succinate, glycolate, glycerate, acetate, palmitate, myristate, laurate, caprynate, and octanoate, which are related to the citrate cycle, glyoxylate and dicarboxylate metabolism, and fatty acid biosynthesis. In conclusion, this study suggests that inhalation of VOCs during horticultural activities can help alleviate depression and depressive moods.